Pengaruh Konflik Kerja dan Stress Kerja Terhadap Kinerja Pegawai Pada Dinas Pertambangan dan Energi Pemerintah Kabupaten Kepulauan Meranti Riau - Yapentra, Arhipen; Weni, Ratna (Eko dan Bisnis: Riau Economic and Business Review, 2016)
The Research this aims to determine the effect of work conflict and job stress on employee performance At the Department of Mines and Energy District Meranti Islands. Collecting data using a questionnaire, distributed to 32 respondents drawn using the full sample. Analysis of data using multiple linear regression analysis with SPSS 17 for Windows. The results showed that there is a positive significant effect on the labor conflict on employee performance. It can be seen that t value > t table (2.863>2.052) and probability 0,008< 0.05. There is a significant negative effect of work stress on employee performance. It can be seen that t count > t table (-2.512> 2.052) and probability (0.142)>0.05. Based on the calculation of F test obtained by F value>F table (4.829>3.55) and a probability value of 0.016 <0.05 means work conflict and work stress together a significant effect on the performance of employees. The coefficient of determination R Square value of 0.263 indicated that contributed employee performance changes of 26,3% influenced by work conflict and work stress of employee